Philippines - Mi-ing, Julie Grace Kalngan (English Education Department, 2023)
To speak intelligibly is a goal in speaking to be understood in oral communication with a second language. Mistakes even in simple sounds may deter the correct flow of meanings to the listeners. Thus, this study determined the most critical vowel and consonant contrastive sounds among Grade 7 learners of Bontoc, Mountain Province. A Phonetic Diagnostic Test (PDT) was administered to learners, and then the tests were checked, tabulated, and interpreted. The results were computed using the weighted mean and frequency. The salient findings of the study determined the most critical vowel and consonant contrastive sounds among Bontok learners of L2 which are /æ/ - /α/, /u/ - /ʊ/ and /O/ - /ɔ/, /i/ - /I/, /Ө/ - /t/, /ð/ - /d/, and /tʃ/ -/dʒ/.